Análisis a resistencia a la insulina como incrementador a la glucosa sanguínea en pacientes con sobre peso con el método quimioluminescencia Pasaje - Orellana Ortiz, Cruz L. (2015)
The insulin resistance is characterized by one diminished capacity of insulin to perform normal physiological functions. Usually precedes clearly pathological situations such as type 2 diabetes mellitus or metabolic syndrome and is associated with conditions such as overweight or obese. Also of note other circumstances such as age, pregnancy and polycystic ovary where the insulin resistance plays an important role initially, insulin resistance generates compensatory mechanisms, such that during a period of time, the hypersecretion of insulin keep blood sugar under control. This period could be called prediabetic turn out difficult to detect from a clinical point of view, precisely by keeping blood glucose levels within normal limits. However, this situation deteriorates progressively to occur the called pancreatic failure, when the beta cells are not able to maintain the hypersecretion of insulin, but which start to deteriorate decreasing insulin secretion. This is the point where you usually start to diagnose most cases of type 2 diabetes mellitus and metabolic syndrome.